Utilisation of organic compounds by osmotrophic algae in an acidic lake of Patagonia (Argentina) - Beamud, Sara Guadalupe (2014)
We investigated whether algal osmotrophy in naturally acidic Lake Caviahue is an important process for acquisition of organic carbon and organic nitrogen. To accomplish this, we quantified algal assimilation of organic compounds, measured the specific growth rate and biomass yield, and documented incorporation of organic compounds by phytoplankton in situ using microautoradiography. Substrate uptake quantification and microautoradiographic investigations were performed using 3 H-leucine, 3 H-glucose, 3 H-thymidine, 14C-aspartic acid, 14C-acetic acid and 14C-bicarbonates. The results showed that the most important species of the phytoplankton community, Keratococcus rhaphidioides and Watanabea sp., took up various sources of organic carbon and nitrogen under both light and dark conditions. They were also able to assimilate leucine, thymidine, aspartic acid and acetate under high levels of inorganic nitrogen and phosphorus, while they could use leucine, arginine, glutamine and glucose under low levels of nitrogen and phosphorus. The assimilation rates were higher in light than in darkness, and the algal specific growth rates increased when organic sources were added. We proposed that osmotrophy complements the main photosynthetic process of the phytoplankton in Lake Caviahue, which helps to overcome the scarcity of light and inorganic nitrogen and carbon in the water column.